Kepemimpinan Efektif di Madrasah Meningkatkan Mutu - Ika Astuti; Sumarmi Sumarmi; Mochammad Eka Mahmud (Journal on Education, 2023)
Education can develop optimally if all parties around education are able to work together to provide the best contribution according to their abilities. One of them is the participation of parents and the community. This research aims to identify and then describe the role of public relations from educational institutions in involving parents and the community in early childhood education institutions. This research uses qualitative methods with literacy studies or literature studies. Research results: educational institutions must carry out good public relations management so that goals can be realized. Education management carried out by institutions includes planning, organizing, implementing, monitoring and evaluating how to involve parents and the community, including: how parents meet children's learning needs, how institutions can utilize the community as a school resource, how to build relationships, communication and mutual trust. parents and society.